Poškodbe izteznega aparata kolena - Gregorič, Gašper (Medicinski razgledi, 2000)
The paper is an overview of the injuries of the extensor mechanism of the knee, which include ruptures of the quadriceps muscle tendon and patellar tendon, as well as patellar fructures. The anatomical and biomechanical characteristics, mechanism of injury, diagnosis, methods of treatment, rehabilitation and prognosis are described.
Keywords: Knee injuries; kolenski sklep; Diagnosis; poškodbe; Surgery; tetive; Rehabilitation; kirurško zdravljenje; Patella; Injuries; Patellar ligament; Biomechanics; Tendon injuries